Design Of Tumor Image Data Server Aplication Using ITK Library (Insight Toolkit) - Meikolin Saimara (IHSA Institute, 2020)
In the medical image processing of brain tumors, it is not only focused on the results of CT Scans and MRIs but also supporting software for analyzing brain tumor diseases. Every medical device requires a high specification computer to analyze the disease and this requires a lot of computers so that it requires a lot of funds plus the efficiency of the time needed in the image processing process. ITK is software that will be used to analyze tumors. In saving funds and time efficiency, a centralized computer system based on a network is needed, namely SOAP web service technology.The data to be used is the result of MRI with DICOM format. The system consists of a client application and a server application, the programming language used is C # (C Sharp). The client will send a slice of brain tumor image data on the server and the server will process the image data by segmenting the image data with the threshold segmentation method that is already available on the ITK software and will display the results of segmentation and brain tumor area on the client. Based on the test results, the area of ​​the brain tumor in a slice of 4.45 cm2 by increasing the threshold value will reduce noise and also affect the area of ​​the brain tumor. In testing the system using a standalone computer, the processing time obtained is 2.12 by testing a network-based system using a web service with one client, the processing time is 4.16 seconds, but the results of the black area obtained from the segmentation process are as large as 28.89 cm2. In the addition of four clients, the time difference is obtained by seconds in progress.